2010
DOI: 10.1590/s1806-37132010000200006
|View full text |Cite
|
Sign up to set email alerts
|

Competence of senior medical students in diagnosing tuberculosis based on chest X-rays

Abstract: Objective: To evaluate the competence of senior medical students in diagnosing tuberculosis (TB) based on their reading of chest X-rays, as well as to identify the factors associated with high scores for the overall interpretation of chest X-rays. Methods: In October 2008, a convenience sample of senior medical students who had undergone formal training in radiology at the Federal University of Rio de Janeiro School of Medicine, in the city of Rio de Janeiro, Brazil, were invited to participate in the study. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…On a different note, Lourenção et al34 highlight the relationship between health and quality of life among the resident medical staff and find that an adequate training program is needed not only to increase professional qualification and personal quality of life, but also to provide safety during patient treatment. Silva et al35 evaluated the competence of senior medical students in diagnosing tuberculosis based on their reading of chest X-rays and found that in this sample of medical students, who had received formal training in radiology early in their medical school course, the competence in interpreting the chest X-rays of TB patients was good. Since being introduced as an elective discipline (non-obligatory) in the second semester of 2002, acupuncture has been taught in the University of São Paulo School of Medicine.…”
Section: Reviewmentioning
confidence: 96%
“…On a different note, Lourenção et al34 highlight the relationship between health and quality of life among the resident medical staff and find that an adequate training program is needed not only to increase professional qualification and personal quality of life, but also to provide safety during patient treatment. Silva et al35 evaluated the competence of senior medical students in diagnosing tuberculosis based on their reading of chest X-rays and found that in this sample of medical students, who had received formal training in radiology early in their medical school course, the competence in interpreting the chest X-rays of TB patients was good. Since being introduced as an elective discipline (non-obligatory) in the second semester of 2002, acupuncture has been taught in the University of São Paulo School of Medicine.…”
Section: Reviewmentioning
confidence: 96%
“…No Brasil o treinamento em radiologia e diagnóstico por imagem não é obrigatório nas escolas médicas. (Silva et al, 2010). O ensino da radiologia na graduação médica vem sendo estudada na literatura internacional há algum tempo, pois a radiologia é uma especialidade crucial no manejo do paciente e que está no cenário médico desde o início do século XIX.…”
Section: Discussionunclassified
“…Such findings demonstrate a clear deficiency in the education of the professionals included in the present study, who increasingly request exams whose basic principles are unknown by most of them. In Brazil, the training in radiology and imaging diagnosis is not mandatory in medical schools, a fact which can lead to wide variation and heterogeneity of curricula, providing, according to many authors, less than would be necessary (22) .…”
Section: Discussionmentioning
confidence: 99%